Kalibrasi Jangka Sorong Nonius (Vernier Calliper) Berdasarkan Standar Jis B 7507 Di Laboratorium Pengukuran Teknik Mesin Universitas Riau - Arief, Dodi Sofyan; Amani, Nahrul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Vernier calliper is very much used either by measurement laboratories and production. Vernier calliper measurement tools necessary to calibrate each period of 12 months, with a calibration done will determine the value of the correction/error and the value of the measurement uncertainty of measuring instruments vernier calliper. In this study calibration of vernier calliper follow the standard JIS B 7507 - 1993 at which the standard has been described specification requirements vernier calliper. Based on the results of the calibration has been done vernier calliper I have a maximum error of 0.00042 mm and the value of the uncertainty confidence level at 95% with a coverage factor of k = 2 is U95 = ±59.02 μm, vernier callipers II has a maximum error of 0.01994 mm and uncertainties confidence level at 95% with a coverage factor of k = 2 is U95 = ±59.42 μm. Both vernier callipers meets the requirements based on JIS B 7507-1993.Keywords: Metrology, Calibration, Vernier Calliper